46. Somatosensory evoked potentials in neonatal hypoxic-ischemic encephalopathy. Issue 12 (December 2017) - De Luca, M.; Pro, S.; Alessandri, B.; Longo, D.; Savarese, I.; Dotta, A.; Agatiello, M.; Toffoli, E.; Suppiej, A.; Di Capua, M.
Abstract : Somatosensory evoked potentials (SEPs) are considered a useful exam for the prognosis of newborns with hypoxic-ischemic encephalopathy (HIE) treated with hypothermia. We examined our data in respect to the MRI, considering the repetitivity of the abnormalities of the SEPs in the time. Of a large number of newborns evaluated with HIE treated with hypothermia in both centers we considered a group of patients with SEPs and MRI just after the completion of hypothermia. 10 patients with abnormal SEPs have repeated the exam after a period ranging from 4 days to 7 months: in 7 cases the SEPs were normalized (in 3 newborns just after few weeks). In conclusion, we think that SEPs abnormalities in neonatal HIE have to be confirmed for a possible role in the prognosis.